Educação e Práticas Comunitárias: urgências e desafios: Education and Community Practices: urgencies and challenges - Gonçalves, Jean Carlos; Gomes da Silva, Maria de Fátima; Garcia Marcelino, Carla Saul (Revista Cocar, 2023)
Apresentação do dossiê: Educação e Práticas Comunitárias Presentation of the dossier: Education and Community Practices